2021
DOI: 10.1038/s41598-021-00923-1
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter Spanish study of atropine 0.01% in childhood myopia progression

Abstract: To evaluate the efficacy and safety of atropine 0.01% eye drops for myopia control in a multicentric pediatric Spanish cohort. An interventional, prospective, multicenter study was designed. Children aged between 6 and 14 years, with myopia between − 2.00 D to − 6.00 D, astigmatism < 1.50 D and documented previous annual progression greater than − 0.5 D (cycloplegic spherical equivalent, SE) were included. Once nightly atropine 0.01% eye drops in each eye were prescribed to all participants for 12 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 46 publications
(55 reference statements)
1
13
0
2
Order By: Relevance
“…In the Low-Concentration Atropine for Myopia Progression (LAMP) study, 0.01% atropine, despite its inferior efficacy compared with 0.025% and 0.05% atropine, still showed a 27% and 27.7% reduction in myopia progression 1 and 2 years after treatment, respectively 20,21 . Other studies have also demonstrated the efficacy of 0.01% atropine in treating childhood myopia [22][23][24][25][26][27][28][29][30][31][32][33][34] . However, limited information is available concerning who would benefit most…”
mentioning
confidence: 99%
“…In the Low-Concentration Atropine for Myopia Progression (LAMP) study, 0.01% atropine, despite its inferior efficacy compared with 0.025% and 0.05% atropine, still showed a 27% and 27.7% reduction in myopia progression 1 and 2 years after treatment, respectively 20,21 . Other studies have also demonstrated the efficacy of 0.01% atropine in treating childhood myopia [22][23][24][25][26][27][28][29][30][31][32][33][34] . However, limited information is available concerning who would benefit most…”
mentioning
confidence: 99%
“…Perez-Flores et al conducted a multicenter study that also proved 0.01% atropine eye drops have efficacy and safety in a Spanish cohort [ 18 ]. Mean SE progression before treatment was −1.01 (SD 0.38) D a year versus −0.44 (SD 0.41) D a year while using 0.01% atropine eye drops ( p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…In a Spanish cohort a mean increase of 0.74 mm in pupil diameter (PD) was observed when using 0.01% atropine eye drops [ 18 ]. Cyphers and colleagues evaluated symptoms and ocular findings associated with the use of 0.01% atropine eye drops for one week in young adults aged 21–30 years [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies corroborate the use of cycloplegics in treating childhood myopia through the significant increase in choroidal thickness; however, treatment with cyclopentolate is not recommended due to other cycloplegics with a longer duration of effect. [47][48][49][50][51] Anterior Segment Analgesics…”
Section: Treatment Of Childhood Myopiamentioning
confidence: 99%